The politics of American religious identity : the seating of Senator Reed Smoot, Mormon apostle - Flake, Kathleen (Legal classics library., 2004)
Between 1901 and 1907, a coalition of Protestant churches sought to expel newly elected Reed Smoot from the Senate for being a Mormon. Here, Kathleen Flake shows how the subsequent investigative hearing ultimately mediated a compromise between Progressive Era Protestantism and Mormonism and resolved the nation's long-standing "Mormon Problem."